Readiness of Hospitals at Deli Serdang Regency and Pematang Siantar City Responding to The Covid-19 Pandemic: Implementation of the N-CovHospital Readiness - EL- Matury, Herlina Jamaludin; Nabila Syahlan; Fatma Lestari; Mohd Rafee B. Baharuddin (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
During the COVID-19 pandemic, hospitals faced tremendous pressure to handle the surge of patients while maintaining essential health services, and many were unprepared for such an unprecedented situation. Hospitals play a critical role in disaster response by providing medical care to affected populations. This study aims to evaluate the readiness of hospitals in Deli Serdang Regency and Pematang Siantar City, North Sumatra, in responding to the COVID-19 pandemic using the WHO Rapid Hospital Readiness Checklist for COVID-19. A cross-sectional survey was involving evaluators from three hospitals in Deli Serdang and two hospital in Pematang Siantar. The checklist consisted of 12 key elements covering essential components of hospital preparedness. Results showed that hospitals in Deli Serdang demonstrated high levels of readiness, with scores above 80%, categorized as Level A (high readiness). In contrast, RSUD DJS in Pematang Siantar achieved a readiness score of 59.6%, categorized as Level B (moderate readiness), indicating the need for improvement in prevention and control efforts. Meanwhile, RSU HRP reached 82%, also categorized as Level A. In conclusion, hospitals in Deli Serdang Regency showed strong preparedness in facing the COVID-19 pandemic, while RSUD DJS in Pematang Siantar requires enhancement in planning, inter-unit coordination, and monitoring to strengthen overall readiness. The findings provide valuable insights for policymakers and healthcare professionals to improve hospital preparedness and resilience in future public health emergencies